Focal mechanisms and tectonic stress field in the Valley of Mexico from local seismicity - Delia Iresine Bello Segura; Luis Quintanar Robles; Shri Krishna Singh (Geofísica Internacional)
We performed a comprehensive analysis of the seismic activity in the Valley of Mexico using the records of nearby seismic stations. Events with a high signal-to-noise ratio were chosen, i.e., where the P and S arrivals were sufficiently clear to be distinguishable. Focal mechanisms were obtained for 24 local earthquakes by means of moment tensor inversion using the ISOLA and INVERS2 software packages, finding that most of the seismicity of the Mexico Basin presents normal and strike-slip faulting. Based on the distribution of seismicity within the Valley of Mexico, we identified five areas where the activity is concentrated: Sierra de las Cruces, Central area, Southeastern area, Lake-bed area, and Sierra Chichinautzin. After carrying out a stress field inversion in each region, we found a predominantly extensional tectonic regime with small strike-slip components.. In general, the stress field found is not homogeneous over all areas, indicating complexity in the characteristics and distribution of faulting types. This complexity could be the manifestation of the transtensional stress field in the central part of the Trans-Mexican Volcanic Belt because of the oblique direction of this geological feature relative to the Middle America Trench.